A direct action for GH in improvement of oocyte quality in poor-responder patients - Weall, B.; Al-Samerria, S.; Conceicao, J.; Yovich, John; Almahbobi, Ghanim (BioScientifica Ltd., 2015)
Declining female fecundity at later age and the increasing tendency for women to delay childbirth have lead to a drastic rise in the number of women seeking assisted reproductive technology. Many women fail to respond adequately to standard ovarian stimulation regimens, raising a significant therapeutic challenge. Recently, we have demonstrated that the administration of GH, as an adjunct to ovarian stimulation, has improved the clinical outcomes by enhancing the oocyte quality. However, the mechanism(s) by which GH facilitated this improvement is yet to be understood. This study aimed to determine these potential mechanism(s) through the use of immunofluorescent localisation of GH receptors (GHRs) on the human oocyte and unbiased computer-based quantification to assess and compare oocyte quality between women of varying ages, with or without GH treatment. This study demonstrates for the first time, the presence of GHRs on the human oocyte. The oocytes retrieved from older women showed significant decrease in the expression of GHRs and amount of functional mitochondria when compared with those from younger patients. More interestingly, when older patients were treated with GH, a significant increase in functional mitochondria was observed in their oocytes. We conclude that GH exerts a direct mode of action, enabling the improvement of oocyte quality observed in our previous study, via the upregulation of its own receptors and enhancement of mitochondrial activity. This result, together with recent observations, provides scientific evidence in support of the use of GH supplementation for the clinical management of poor ovarian response.